Physiological and transcriptomic analysis uncovers salinity stress mechanisms in a facultative crassulacean acid metabolism plant Dendrobium officinale - Zhang, Mingze; Liu, Nan; Teixeira da Silva, Jaime A.; Liu, Xuncheng; Deng, Rufang; Yao, Yuxian; Duan, Jun; He, Chunmei (Frontiers in Plant Science, 2022)
Dendrobium officinale is a precious medicinal Chinese herb that employs facultative crassulacean acid metabolism (CAM) and has a high degree of abiotic stress tolerance, but the molecular mechanism underlying the response of this orchid to abiotic stresses is poorly understood. In this study, we analyzed the root microstructure of D. officinale plantlets and verified the presence of chloroplasts by transmission electron microscopy. To obtain a more comprehensive overview of the molecular mechanism underlying their tolerance to abiotic stress, we performed whole‐transcriptome sequencing of the roots of 10-month-old plantlets exposed to salt (NaCl) treatment in a time‐course experiment (0, 4 and 12 h). The total of 7376 differentially expressed genes that were identified were grouped into three clusters (P < 0.05). Metabolic pathway analysis revealed that the expression of genes related to hormone (such as auxins, cytokinins, abscisic acid, ethylene and jasmonic acid) biosynthesis and response, as well as the expression of genes related to photosynthesis, amino acid and flavonoid metabolism, and the SOS pathway, were either up- or down-regulated after salt treatment. Additionally, we identified an up-regulated WRKY transcription factor, DoWRKY69, whose ectopic expression in Arabidopsis promoted seed germination under salt tress. Collectively, our findings provide a greater understanding of the salt stress response mechanisms in the roots of a facultative CAM plant. A number of candidate genes that were discovered may help plants to cope with salt stress when introduced via genetic engineering.